Aging-resistant tile adhesive for external wall insulation system and application thereof

CN118344095BActive Publication Date: 2026-10-23JIANGSU YONGYANG NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410467888.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-18
Publication Date
2026-10-23
Estimated Expiration
2044-04-18

AI Technical Summary

Benefits of technology

[0021]本发明制备得到的瓷砖粘结剂具有优异的粘结性,符合C2ES1 JC/T547-2017标准,不仅具有优异的耐候性,还具有一定的助保温性能;同时本发明制备得到的瓷砖粘结剂户外施工环境要求较低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004797991300000021
    Figure BDA0004797991300000021
  • Figure BDA0004797991300000022
    Figure BDA0004797991300000022
  • Figure BDA0004797991300000031
    Figure BDA0004797991300000031
Patent Text Reader

Abstract

The application relates to the technical field of building, in particular to an anti-aging ceramic tile adhesive for an external wall thermal insulation system and application. The anti-aging ceramic tile adhesive for the external wall thermal insulation system is prepared from the following raw materials: Portland cement, modified latex powder, cellulose ether, defoaming agent, thixotropic lubricant, high molecular polymer and ultraviolet absorber. The ceramic tile adhesive prepared by the application has excellent adhesion and meets the C2ES1JC / T547-2017 standard, has excellent weather resistance and certain thermal insulation assisting performance, and has low requirements on outdoor construction environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building technology, and in particular to an aging-resistant ceramic tile adhesive for external wall insulation systems and its application. Background Technology

[0002] Tile adhesive is a powdered bonding material made primarily of high-quality cement, high-quality quartz sand, and polymer adhesives, along with various additives in precise proportions, mixed evenly in a mixer. It has a certain degree of flexibility and fundamentally solves problems such as cracking, hollowing, detachment, and leakage in building decoration and renovation.

[0003] The operating temperature of tile adhesive is between 5℃ and 35℃. A construction temperature exceeding 35℃ not only poses a significant challenge to the health of construction workers, but is also very detrimental to the use of tile adhesive.

[0004] High temperatures can cause tile adhesive to thicken during use due to rapid evaporation of moisture or solvents. Furthermore, during the film-forming process, inconsistent drying rates between the surface and interior of the adhesive layer can lead to difficulties in film formation, blistering, shrinkage, and cracking. When tiling during periods of excessively high summer temperatures, it's advisable to sprinkle water indoors and wait until the temperature reaches a suitable level before proceeding with the tiling process.

[0005] Outdoor tile adhesives require higher requirements for aging resistance, and even higher requirements for outdoor large-format slabs. Summary of the Invention

[0006] To solve the above-mentioned technical problems, the present invention provides an aging-resistant ceramic tile adhesive for external wall insulation systems, the raw materials of which include:

[0007] Silicate cement, modified latex powder, cellulose ether, defoamer, thixotropic lubricant, polymer, ultraviolet absorber.

[0008] As one embodiment of the present invention, the raw materials for its preparation include:

[0009]

[0010] In one embodiment of the present invention, the raw materials for preparation, by weight, comprise:

[0011]

[0012] As one embodiment of the present invention, the modified latex powder is prepared as follows:

[0013] Add the dissolved polyvinyl alcohol aqueous solution to the mixing tank, start stirring, add EVA emulsion and mix for 30 minutes to obtain a spray liquid with a certain solid content and viscosity; spray dry the spray liquid to obtain modified latex powder.

[0014] In one embodiment of the present invention, the silicate cement has a strength grade of 42.5R and an alkali content controlled at ≤1%.

[0015] In one embodiment of the present invention, the polymer is an acrylic-modified polyurethane adhesive.

[0016] As one embodiment of the present invention, the raw materials for preparing the acrylic modified polyurethane adhesive include: 50-80 parts of polyurethane acrylate, 10-40 parts of reactive diluent, and 2-10 parts of modified rosin resin.

[0017] As one embodiment of the present invention, the raw materials for preparing the polyurethane acrylate include: 45-55 parts of polyol, 8-15 parts of polyisocyanate, 2-8 parts of 6-hydroxyhexyl acrylate, and 0.01-0.05 parts of catalyst.

[0018] In one embodiment of the present invention, the ultraviolet absorber is BASF ultraviolet absorber 234.

[0019] A second aspect of the present invention provides an aging-resistant ceramic tile adhesive for an external wall insulation system, characterized in that it is used in the building materials field.

[0020] By adopting the above technical solution, the present invention has the following beneficial effects:

[0021] The tile adhesive prepared by this invention has excellent adhesion and meets the C2ES1 JC / T547-2017 standard. It not only has excellent weather resistance but also has certain thermal insulation properties. At the same time, the tile adhesive prepared by this invention has low requirements for outdoor construction environment. Detailed Implementation

[0022] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] This invention provides an aging-resistant ceramic tile adhesive for external wall insulation systems, wherein the raw materials for its preparation, by weight, comprise:

[0024]

[0025] Silicate cement

[0026] In this invention, the silicate cement has a strength grade of 42.5R and an alkali content controlled at ≤1%. It was purchased from Jiangsu Yangzi Cement Co., Ltd. and its model is P0 42.5.

[0027] Modified latex powder

[0028] The modified latex powder is prepared as follows in this invention:

[0029] Add a 20wt% aqueous solution of polyvinyl alcohol (molecular weight 2000) to the reactor, start stirring, add EVA emulsion with a degree of alcoholysis of 40% and mix and stir for 30 minutes to obtain a spray liquid with a solid content of 40%.

[0030] The spray liquid is slowly heated to 60°C for spray drying; the system is run idle, maintaining a negative pressure of -0.1MPa in the drying tower; the inlet air is heated, and when the inlet air temperature reaches 150°C, the system is started to maintain the outlet temperature at around 85°C; after the temperature stabilizes, the inorganic additive addition system and the feeding system are turned on, allowing the spray-dried particles and dispersant to mix thoroughly in the drying tower. After dust collection, cooling, and dehumidification, redispersible latex powder is obtained. The inorganic additive is TiO2 powder (50nm), and the mass ratio of TiO2 powder to the spray liquid is 1:30.

[0031] Cellulose ethers

[0032] The cellulose ether described in this invention was purchased from Zhejiang Zhiwei New Material Technology Co., Ltd., and its model number is MP100H.

[0033] Defoamer

[0034] In this invention, the defoamer is a compound of two defoamers, specifically Jiangsu Liwenjia Chemical Co., Ltd.'s 658 and Changzhou Youchang New Materials Co., Ltd.'s YC-216, in a mass ratio of 3:1.

[0035] Thixotropic lubricant

[0036] In this invention, the thixotropic lubricant is ET-2000 from Suzhou Kaibei Chemical Co., Ltd.

[0037] polymer

[0038] The polymer is an acrylic-modified polyurethane adhesive.

[0039] As one embodiment of the present invention, the raw materials for preparing the acrylic modified polyurethane adhesive include: 50-80 parts of polyurethane acrylate, 10-40 parts of reactive diluent, and 2-10 parts of modified rosin resin.

[0040] In one embodiment of the present invention, the raw materials for preparing the polyurethane acrylate include: 45-55 parts of polyol, 8-15 parts of 4,4'-dicyclohexylmethane diisocyanate, 2-8 parts of 6-hydroxyhexyl acrylate, and 0.01-0.05 parts of dibutyltin dilaurate. The preparation process of the polyurethane acrylate is as follows: Polytrimethylene ether glycol (SK ECOPROL H2000 from Korea) is weighed according to the weight parts, and dehydrated at 110°C and a vacuum degree of -0.08 to -0.1 MPa for 1 hour. After cooling to 50°C, polyisocyanate is added, and the temperature is raised to 80-85°C and reacted for 3 hours. After cooling to 60°C, 6-hydroxyhexyl acrylate and dibutyltin dilaurate are added, and the reaction is carried out at 60-65°C for 3 hours. Tetrahydrofuran acrylate and TPO photoinitiator are added, and the mixture is stirred at 60°C for 0.5 hours at a stirring speed of 600 r / min. After stirring is completed, polyurethane acrylate is obtained.

[0041] As one embodiment of the present invention, the acrylic modified polyurethane adhesive is prepared by stirring polyurethane acrylate, ethyl acetate, and modified rosin resin at high speed for 30 minutes.

[0042] The modified rosin resin is prepared as follows: Take 70 parts of rosin, heat and melt it under nitrogen, then add 8 parts of 3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride and 4 parts of propylene glycol. Start the stirrer and stir, raise the temperature to 180-200℃ and keep it at that temperature for 30 minutes to obtain the modified rosin resin.

[0043] UV absorber

[0044] In this invention, the ultraviolet absorber is BASF ultraviolet absorber 234.

[0045] The tile adhesive prepared by this invention not only meets the highest standards but also exhibits good weather resistance and is suitable for thermal insulation systems. While air possesses excellent thermal insulation properties, the tile adhesive prepared by this invention not only utilizes these properties but also possesses excellent adhesion. This is because the modified latex powder and rosin resin allow the modified latex powder to continuously adhere to the cavities created by silicate cement, thereby improving the product's strength and adhesion while maintaining some space, thus achieving both adhesion and thermal insulation simultaneously.

[0046] The present invention will be further explained below with reference to specific embodiments.

[0047] Example 1

[0048] This embodiment provides an aging-resistant ceramic tile adhesive for external wall insulation systems, the raw materials of which include:

[0049] 26 parts of silicate cement (the silicate cement has a strength grade of 42.5R and an alkali content controlled at ≤1%, specifically purchased from Jiangsu Yangzi Cement Co., Ltd., model P0 42.5)

[0050] 17 parts modified latex powder

[0051] Cellulose ether (Zhejiang Zhiwei New Material Technology Co., Ltd., model MP100H) 6 parts

[0052] 3 parts of defoamer (Jiangsu Liwenjia Chemical Co., Ltd. 658 and Changzhou Youchang New Material Co., Ltd. YC-216, mass ratio 3:1)

[0053] Thixotropic lubricant (the thixotropic lubricant is ET-2000 from Suzhou Kaibei Chemical Co., Ltd.) 2 parts, high molecular polymer 41 parts

[0054] Four parts of ultraviolet absorber (BASF UV absorber 234).

[0055] The modified latex powder is prepared as follows:

[0056] Add a 20wt% aqueous solution of polyvinyl alcohol (molecular weight 2000) to the reactor, start stirring, add EVA emulsion with a degree of alcoholysis of 40% and mix and stir for 30 minutes to obtain a spray liquid with a solid content of 40%.

[0057] The spray liquid is slowly heated to 60°C for spray drying; the system is run idle, maintaining a negative pressure of -0.1MPa in the drying tower; the inlet air is heated, and when the inlet air temperature reaches 150°C, the system is started to maintain the outlet temperature at around 85°C; after the temperature stabilizes, the inorganic additive addition system and the feeding system are turned on, allowing the spray-dried particles and dispersant to mix thoroughly in the drying tower. After dust collection, cooling, and dehumidification, redispersible latex powder is obtained. The inorganic additive is TiO2 powder (50nm), and the mass ratio of TiO2 powder to the spray liquid is 1:30.

[0058] The raw materials for preparing the acrylic-modified polyurethane adhesive include: 56 parts of polyurethane acrylate, 12 parts of ethyl acetate, and 6 parts of modified rosin resin.

[0059] The raw materials for preparing the polyurethane acrylate include: 49 parts of polytrimethylene ether glycol, 9 parts of 4,4'-dicyclohexylmethane diisocyanate, 4 parts of 6-hydroxyhexyl acrylate, and 0.02 parts of dibutyltin dilaurate. The preparation process of the polyurethane acrylate is as follows: Polytrimethylene ether glycol (SK ECOPROL H2000 from Korea) is weighed according to the weight parts and dehydrated for 1 hour at 110℃ and a vacuum degree of -0.08 to -0.1 MPa. After cooling to 50℃, dicyclohexylmethane diisocyanate is added, and the mixture is heated to 80-85℃ and reacted for 3 hours. After cooling to 60℃, 6-hydroxyhexyl acrylate and dibutyltin dilaurate are added, and the mixture is reacted at 60-65℃ for 3 hours. Tetrahydrofuran acrylate and TPO photoinitiator are added, and the mixture is stirred at 60℃ for 0.5 hours at a stirring speed of 600 r / min. After stirring is complete, polyurethane acrylate is obtained.

[0060] The acrylic-modified polyurethane adhesive is prepared as follows: polyurethane acrylate, ethyl acetate, and modified rosin resin are stirred at high speed for 30 minutes to obtain the adhesive.

[0061] The modified rosin resin is prepared as follows: Take 70 parts of rosin, heat and melt it under nitrogen, then add 8 parts of 3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride and 4 parts of propylene glycol. Start the stirrer and stir, raise the temperature to 180-200℃ and keep it at that temperature for 30 minutes to obtain the modified rosin resin.

[0062] Example 2

[0063] This embodiment provides an aging-resistant ceramic tile adhesive for external wall insulation systems, the raw materials of which include:

[0064] 26 parts of silicate cement (the silicate cement has a strength grade of 42.5R and an alkali content controlled at ≤1%, specifically purchased from Jiangsu Yangzi Cement Co., Ltd., model P0 42.5)

[0065] Latex powder (Shanghai Shangnan New Materials Co., Ltd. 4115N) 17 parts

[0066] Cellulose ether (Zhejiang Zhiwei New Material Technology Co., Ltd., model MP100H) 6 parts

[0067] 3 parts of defoamer (Jiangsu Liwenjia Chemical Co., Ltd. 658 and Changzhou Youchang New Material Co., Ltd. YC-216, mass ratio 3:1)

[0068] Thixotropic lubricant (the thixotropic lubricant is ET-2000 from Suzhou Kaibei Chemical Co., Ltd.) 2 parts, high molecular polymer 41 parts

[0069] Four parts of ultraviolet absorber (BASF UV absorber 234).

[0070] The raw materials for preparing the acrylic-modified polyurethane adhesive include: 56 parts of polyurethane acrylate, 12 parts of ethyl acetate, and 6 parts of modified rosin resin.

[0071] The raw materials for preparing the polyurethane acrylate include: 49 parts of polytrimethylene ether glycol, 9 parts of 4,4'-dicyclohexylmethane diisocyanate, 4 parts of 6-hydroxyhexyl acrylate, and 0.02 parts of dibutyltin dilaurate. The preparation process of the polyurethane acrylate is as follows: Polytrimethylene ether glycol (SK ECOPROL H2000 from Korea) is weighed according to the weight parts and dehydrated for 1 hour at 110℃ and a vacuum degree of -0.08 to -0.1 MPa. After cooling to 50℃, dicyclohexylmethane diisocyanate is added, and the mixture is heated to 80-85℃ and reacted for 3 hours. After cooling to 60℃, 6-hydroxyhexyl acrylate and dibutyltin dilaurate are added, and the mixture is reacted at 60-65℃ for 3 hours. Tetrahydrofuran acrylate and TPO photoinitiator are added, and the mixture is stirred at 60℃ for 0.5 hours at a stirring speed of 600 r / min. After stirring is complete, polyurethane acrylate is obtained.

[0072] The acrylic-modified polyurethane adhesive is prepared as follows: polyurethane acrylate, ethyl acetate, and modified rosin resin are stirred at high speed for 30 minutes to obtain the adhesive.

[0073] The modified rosin resin is prepared as follows: Take 70 parts of rosin, heat and melt it under nitrogen, then add 8 parts of 3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride and 4 parts of propylene glycol. Start the stirrer and stir, raise the temperature to 180-200℃ and keep it at that temperature for 30 minutes to obtain the modified rosin resin.

[0074] Example 3

[0075] This embodiment provides an aging-resistant ceramic tile adhesive for external wall insulation systems, the raw materials of which include:

[0076] 26 parts of silicate cement (the silicate cement has a strength grade of 42.5R and an alkali content controlled at ≤1%, specifically purchased from Jiangsu Yangzi Cement Co., Ltd., model P0 42.5)

[0077] 17 parts modified latex powder

[0078] Cellulose ether (Zhejiang Zhiwei New Material Technology Co., Ltd., model MP100H) 6 parts

[0079] 3 parts of defoamer (Jiangsu Liwenjia Chemical Co., Ltd. 658 and Changzhou Youchang New Material Co., Ltd. YC-216, mass ratio 3:1)

[0080] Thixotropic lubricant (the thixotropic lubricant is ET-2000 from Suzhou Kaibei Chemical Co., Ltd.) 2 parts, high molecular polymer 41 parts

[0081] Four parts of ultraviolet absorber (BASF UV absorber 234).

[0082] The modified latex powder is prepared as follows:

[0083] Add a 20wt% aqueous solution of polyvinyl alcohol (molecular weight 2000) to the reactor, start stirring, add EVA emulsion with a degree of alcoholysis of 40% and mix and stir for 30 minutes to obtain a spray liquid with a solid content of 40%.

[0084] The spray liquid is slowly heated to 60°C for spray drying; the system is run idle to maintain the negative pressure of the drying tower at -0.1MPa; the air inlet is heated, and when the air inlet temperature of the drying tower reaches 150°C, the system is started to maintain the outlet temperature at around 85°C; after the temperature stabilizes, dust is collected, and the system is cooled and dehumidified to obtain redispersible latex powder.

[0085] The raw materials for preparing the acrylic-modified polyurethane adhesive include: 56 parts of polyurethane acrylate, 12 parts of ethyl acetate, and 6 parts of modified rosin resin.

[0086] The raw materials for preparing the polyurethane acrylate include: 49 parts of polytrimethylene ether glycol, 9 parts of 4,4'-dicyclohexylmethane diisocyanate, 4 parts of 6-hydroxyhexyl acrylate, and 0.02 parts of dibutyltin dilaurate. The preparation process of the polyurethane acrylate is as follows: Polytrimethylene ether glycol (SK ECOPROL H2000 from Korea) is weighed according to the weight parts and dehydrated for 1 hour at 110℃ and a vacuum degree of -0.08 to -0.1 MPa. After cooling to 50℃, dicyclohexylmethane diisocyanate is added, and the mixture is heated to 80-85℃ and reacted for 3 hours. After cooling to 60℃, 6-hydroxyhexyl acrylate and dibutyltin dilaurate are added, and the mixture is reacted at 60-65℃ for 3 hours. Tetrahydrofuran acrylate and TPO photoinitiator are added, and the mixture is stirred at 60℃ for 0.5 hours at a stirring speed of 600 r / min. After stirring is complete, polyurethane acrylate is obtained.

[0087] The acrylic-modified polyurethane adhesive is prepared as follows: polyurethane acrylate, ethyl acetate, and modified rosin resin are stirred at high speed for 30 minutes to obtain the adhesive.

[0088] The modified rosin resin is prepared as follows: Take 70 parts of rosin, heat and melt it under nitrogen, then add 8 parts of 3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride and 4 parts of propylene glycol. Start the stirrer and stir, raise the temperature to 180-200℃ and keep it at that temperature for 30 minutes to obtain the modified rosin resin.

[0089] Example 4

[0090] This embodiment provides an aging-resistant ceramic tile adhesive for external wall insulation systems, the raw materials of which include:

[0091] 26 parts of silicate cement (the silicate cement has a strength grade of 42.5R and an alkali content controlled at ≤1%, specifically purchased from Jiangsu Yangzi Cement Co., Ltd., model P0 42.5)

[0092] 17 parts modified latex powder

[0093] Cellulose ether (Zhejiang Zhiwei New Material Technology Co., Ltd., model MP100H) 6 parts

[0094] 3 parts of defoamer (Jiangsu Liwenjia Chemical Co., Ltd. 658 and Changzhou Youchang New Material Co., Ltd. YC-216, mass ratio 3:1)

[0095] Thixotropic lubricant (the thixotropic lubricant is ET-2000 from Suzhou Kaibei Chemical Co., Ltd.) 2 parts, high molecular polymer 41 parts

[0096] Four parts of ultraviolet absorber (BASF UV absorber 234).

[0097] The modified latex powder is prepared as follows:

[0098] Add a 20wt% aqueous solution of polyvinyl alcohol (molecular weight 2000) to the reactor, start stirring, add EVA emulsion with a degree of alcoholysis of 40% and mix and stir for 30 minutes to obtain a spray liquid with a solid content of 40%.

[0099] The spray liquid is slowly heated to 60°C for spray drying; the system is run idle, maintaining a negative pressure of -0.1MPa in the drying tower; the inlet air is heated, and when the inlet air temperature reaches 150°C, the system is started to maintain the outlet temperature at around 85°C; after the temperature stabilizes, the inorganic additive addition system and the feeding system are turned on, allowing the spray-dried particles and dispersant to mix thoroughly in the drying tower. After dust collection, cooling, and dehumidification, redispersible latex powder is obtained. The inorganic additive is TiO2 powder (50nm), and the mass ratio of TiO2 powder to the spray liquid is 1:30.

[0100] The raw materials for preparing the acrylic-modified polyurethane adhesive include: 56 parts of polyurethane acrylate, 12 parts of ethyl acetate, and 6 parts of rosin resin.

[0101] The raw materials for preparing the polyurethane acrylate include: 49 parts of polytrimethylene ether glycol, 9 parts of 4,4'-dicyclohexylmethane diisocyanate, 4 parts of 6-hydroxyhexyl acrylate, and 0.02 parts of dibutyltin dilaurate. The preparation process of the polyurethane acrylate is as follows: Polytrimethylene ether glycol (SK ECOPROL H2000 from Korea) is weighed according to the weight parts and dehydrated for 1 hour at 110℃ and a vacuum degree of -0.08 to -0.1 MPa. After cooling to 50℃, dicyclohexylmethane diisocyanate is added, and the mixture is heated to 80-85℃ and reacted for 3 hours. After cooling to 60℃, 6-hydroxyhexyl acrylate and dibutyltin dilaurate are added, and the mixture is reacted at 60-65℃ for 3 hours. Tetrahydrofuran acrylate and TPO photoinitiator are added, and the mixture is stirred at 60℃ for 0.5 hours at a stirring speed of 600 r / min. After stirring is complete, polyurethane acrylate is obtained.

[0102] The acrylic-modified polyurethane adhesive is prepared as follows: polyurethane acrylate, ethyl acetate, and rosin resin are stirred at high speed for 30 minutes to obtain the adhesive.

[0103] Example 5

[0104] This embodiment provides an aging-resistant ceramic tile adhesive for external wall insulation systems, the raw materials of which include:

[0105] 26 parts of silicate cement (the silicate cement has a strength grade of 42.5R and an alkali content controlled at ≤1%, specifically purchased from Jiangsu Yangzi Cement Co., Ltd., model P0 42.5)

[0106] 17 parts modified latex powder

[0107] Cellulose ether (Zhejiang Zhiwei New Material Technology Co., Ltd., model MP100H) 6 parts

[0108] 3 parts of defoamer (Jiangsu Liwenjia Chemical Co., Ltd. 658 and Changzhou Youchang New Material Co., Ltd. YC-216, mass ratio 3:1)

[0109] Thixotropic lubricant (the thixotropic lubricant is ET-2000 from Suzhou Kaibei Chemical Co., Ltd.) 2 parts, high molecular polymer 41 parts

[0110] Four parts of ultraviolet absorber (BASF UV absorber 234).

[0111] The modified latex powder is prepared as follows:

[0112] Add a 20wt% aqueous solution of polyvinyl alcohol (molecular weight 2000) to the reactor, start stirring, add EVA emulsion with a degree of alcoholysis of 40% and mix and stir for 30 minutes to obtain a spray liquid with a solid content of 40%.

[0113] The spray liquid is slowly heated to 60°C for spray drying; the system is run idle, maintaining a negative pressure of -0.1MPa in the drying tower; the inlet air is heated, and when the inlet air temperature reaches 150°C, the system is started to maintain the outlet temperature at around 85°C; after the temperature stabilizes, the inorganic additive addition system and the feeding system are turned on, allowing the spray-dried particles and dispersant to mix thoroughly in the drying tower. After dust collection, cooling, and dehumidification, redispersible latex powder is obtained. The inorganic additive is TiO2 powder (50nm), and the mass ratio of TiO2 powder to the spray liquid is 1:30.

[0114] The raw materials for preparing the acrylic-modified polyurethane adhesive include: 56 parts of polyurethane acrylate, 12 parts of ethyl acetate, and 6 parts of modified rosin resin.

[0115] The raw materials for preparing the polyurethane acrylate include: 49 parts of polycaprolactone polyol, 9 parts of 4,4'-dicyclohexylmethane diisocyanate, 4 parts of 6-hydroxyhexyl acrylate, and 0.02 parts of dibutyltin dilaurate. The preparation process of the polyurethane acrylate is as follows: Polycaprolactone polyol is weighed according to the weight percentage and dehydrated for 1 hour at 110℃ and a vacuum of -0.08 to -0.1 MPa. After cooling to 50℃, dicyclohexylmethane diisocyanate is added, and the mixture is heated to 80-85℃ and reacted for 3 hours. The mixture is then cooled to 60℃, and 6-hydroxyhexyl acrylate and dibutyltin dilaurate are added. The mixture is reacted at 60-65℃ for 3 hours. Tetrahydrofuran acrylate and TPO photoinitiator are added, and the mixture is stirred at 60℃ for 0.5 hours at a stirring speed of 600 r / min. After stirring is complete, the polyurethane acrylate is obtained.

[0116] The acrylic-modified polyurethane adhesive is prepared as follows: polyurethane acrylate, ethyl acetate, and modified rosin resin are stirred at high speed for 30 minutes to obtain the adhesive.

[0117] The modified rosin resin is prepared as follows: Take 70 parts of rosin, heat and melt it under nitrogen, then add 8 parts of 3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride and 4 parts of propylene glycol. Start the stirrer and stir, raise the temperature to 180-200℃ and keep it at that temperature for 30 minutes to obtain the modified rosin resin.

[0118] Example 6

[0119] This embodiment provides an aging-resistant ceramic tile adhesive for external wall insulation systems, the raw materials of which include:

[0120] 26 parts of silicate cement (the silicate cement has a strength grade of 42.5R and an alkali content controlled at ≤1%, specifically purchased from Jiangsu Yangzi Cement Co., Ltd., model P0 42.5)

[0121] 17 parts modified latex powder

[0122] Cellulose ether (Zhejiang Zhiwei New Material Technology Co., Ltd., model MP100H) 6 parts

[0123] 3 parts of defoamer (Jiangsu Liwenjia Chemical Co., Ltd. 658 and Changzhou Youchang New Material Co., Ltd. YC-216, mass ratio 3:1)

[0124] Thixotropic lubricant (the thixotropic lubricant is ET-2000 from Suzhou Kaibei Chemical Co., Ltd.) 2 parts, high molecular polymer 41 parts

[0125] Four parts of ultraviolet absorber (BASF UV absorber 234).

[0126] The modified latex powder is prepared as follows:

[0127] Add a 20wt% aqueous solution of polyvinyl alcohol (molecular weight 2000) to the reactor, start stirring, add EVA emulsion with a degree of alcoholysis of 40% and mix and stir for 30 minutes to obtain a spray liquid with a solid content of 40%.

[0128] The spray liquid is slowly heated to 60°C for spray drying; the system is run idle, maintaining a negative pressure of -0.1MPa in the drying tower; the inlet air is heated, and when the inlet air temperature reaches 150°C, the system is started to maintain the outlet temperature at around 85°C; after the temperature stabilizes, the inorganic additive addition system and the feeding system are turned on, allowing the spray-dried particles and dispersant to mix thoroughly in the drying tower. After dust collection, cooling, and dehumidification, redispersible latex powder is obtained. The inorganic additive is TiO2 powder (50nm), and the mass ratio of TiO2 powder to the spray liquid is 1:30.

[0129] The raw materials for preparing the acrylic-modified polyurethane adhesive include: 56 parts of polyurethane acrylate, 12 parts of ethyl acetate, and 6 parts of modified rosin resin.

[0130] The raw materials for preparing the polyurethane acrylate include: 49 parts of polytrimethylene ether glycol, 9 parts of 4,4'-dicyclohexylmethane diisocyanate, and 0.02 parts of dibutyltin dilaurate. The preparation process of the polyurethane acrylate is as follows: Polytrimethylene ether glycol (SK ECOPROL H2000 from Korea) is weighed according to the weight parts and dehydrated for 1 hour at 110℃ and a vacuum degree of -0.08 to -0.1 MPa. After cooling to 50℃, dicyclohexylmethane diisocyanate is added, and the mixture is heated to 80-85℃ and reacted for 3 hours. After cooling to 60℃, 6-hydroxyhexyl acrylate and dibutyltin dilaurate are added, and the mixture is reacted at 60-65℃ for 3 hours. Tetrahydrofuran acrylate and TPO photoinitiator are added, and the mixture is stirred at 60℃ for 0.5 hours at a stirring speed of 600 r / min. After stirring is complete, polyurethane acrylate is obtained.

[0131] The acrylic-modified polyurethane adhesive is prepared as follows: polyurethane acrylate, ethyl acetate, and modified rosin resin are stirred at high speed for 30 minutes to obtain the adhesive.

[0132] The modified rosin resin is prepared as follows: Take 70 parts of rosin, heat and melt it under nitrogen, then add 8 parts of 3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride and 4 parts of propylene glycol. Start the stirrer and stir, raise the temperature to 180-200℃ and keep it at that temperature for 30 minutes to obtain the modified rosin resin.

[0133] Performance testing

[0134] The tests were conducted according to JC / T547-2005 "Ceramic Wall and Floor Tile Adhesives", and the results are shown in Table 1.

[0135] Table 1 Performance Test Results

[0136]

[0137] Two internal volumes of 1m³ will be prepared respectively. 3 The sealed space was constructed using concrete bricks. A heater was placed inside the sealed space, and the exterior was coated with a 0.5cm thick layer of ceramic adhesive as described in Examples 1-6, followed by the adhesion of ceramic tiles. The heater was then turned on for 30 minutes, and the surface temperature of the tiles was measured. The test results are shown in Table 2. Five measurements were taken, and the average value was recorded. The room temperature was maintained at 25℃, and the humidity was 42%RH.

[0138] Table 2 Performance Test Results

[0139] Temperature ℃ 27.2 29.6 27.9 27.5 27.4 27.4

[0140] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An aging-resistant ceramic tile adhesive for use in external wall insulation systems, comprising the following raw materials: 26 parts of silicate cement 17 parts modified latex powder 6 parts of cellulose ether Defoamer, 3 parts 2 parts thixotropic lubricant 41 parts of polymer 4 parts of ultraviolet absorber; The modified latex powder is prepared as follows: A 20wt% aqueous solution of polyvinyl alcohol with a molecular weight of 2000 was added to a reactor, and stirring was started. Then, an EVA emulsion with a degree of alcoholysis of 40% was added and stirred for 30 minutes to obtain a spray liquid with a solid content of 40%. The spray liquid is slowly heated to 60°C for spray drying; the system is run idle, maintaining a negative pressure of -0.1MPa in the drying tower; the air inlet is heated, and when the air inlet temperature reaches 150°C, the system is started to maintain the outlet temperature at around 85°C; after the temperature stabilizes, the inorganic additive addition system and the feeding system are turned on, so that the spray-dried particles and the dispersing agent are fully mixed in the drying tower. After dust collection, cooling and dehumidification, redispersible latex powder is obtained; the inorganic additive is TiO2 powder, 50nm, and the mass ratio of TiO2 powder to the spray liquid is 1:

30. The polymer is an acrylic-modified polyurethane adhesive, and the raw materials for preparing the acrylic-modified polyurethane adhesive include: 56 parts of polyurethane acrylate, 12 parts of ethyl acetate, and 6 parts of modified rosin resin. The raw materials for preparing the polyurethane acrylate include: 49 parts of polytrimethylene ether glycol, 9 parts of 4,4'-dicyclohexylmethane diisocyanate, 4 parts of 6-hydroxyhexyl acrylate, and 0.02 parts of dibutyltin dilaurate. The preparation process of the polyurethane acrylate is as follows: Polytrimethylene ether glycol is weighed according to the weight parts, and SK ECOPROL H2000 (Korea) is used to dehydrate it for 1 hour at 110°C and a vacuum degree of -0.08 to -0.1 MPa. After cooling to 50°C, dicyclohexylmethane diisocyanate is added, and the mixture is heated to 80-85°C and reacted for 3 hours. After cooling to 60°C, 6-hydroxyhexyl acrylate and dibutyltin dilaurate are added, and the mixture is reacted at 60-65°C for 3 hours. Tetrahydrofuran acrylate and TPO photoinitiator are added, and the mixture is stirred at 60°C for 0.5 hours at a stirring speed of 600 r / min. After stirring is completed, polyurethane acrylate is obtained. The acrylic-modified polyurethane adhesive is prepared as follows: polyurethane acrylate, ethyl acetate, and modified rosin resin are stirred at high speed for 30 minutes to obtain the adhesive. in, The modified rosin resin is prepared as follows: Take 70 parts of rosin, heat and melt it under nitrogen, then add 8 parts of 3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride and 4 parts of propylene glycol. Start the stirrer and stir, raise the temperature to 180-200℃ and keep it at that temperature for 30 minutes to obtain the modified rosin resin.

2. The aging-resistant ceramic tile adhesive for external wall insulation systems according to claim 1, characterized in that, Used in the building materials industry.

Citation Information

Patent Citations

  • Acrylic ester modified waterborne polyurethane adhesives and preparation method thereof

    CN105315953A

  • Mannan adhesive and preparation method thereof

    CN105505286A

  • EVA type redispersible latex powder and preparation method thereof

    CN110684306A

  • Ceramic tile adhesive mortar and preparation method thereof

    CN111747702A